Analysis of a Public School’s Practices and Values through the Lens of Equitable Quality Education for All: A Case for Juxtaposing Schools and SDGs - Mihiretie, Dawit Mekonnen; Andargie, Tesfaye Ebabuye (Bahir Dar Journal of Education, 2022)
This study examined the hidden curriculum of a primary school embedded in assessment practices and students’ performance. Critical education theorists’ arguments on education, social and cultural reproduction, and Bourdieu’s theory of symbolic capital are used to inform the study. Using a participative observer case study methodology, the study employed interview, observation, and document analysis to collect data. The participants (four students, two teachers, and the principal) of the study were selected using purposive sampling. Thematic analysis was used to analyze the data collected from these participants. The results of the study revealed that school assessment techniques and students’ achievement implicitly and explicitly communicate and institutionalize social stratification in the school which in turn considerably influences students’ access to school resources, school leadership positions, and school communities’ expectations on students. Students, teachers, and the school leadership, wittingly or unwittingly, are active actors in the implicit and explicit socialization process which reinforces values and practices that contradict equitable quality education for all. The findings suggest that policy and Sustainable Development Goals (SDGs) for equitable quality education should heed to actual school and classroom practices, and not merely be assessed based on data that are disaggregated along gender, rural and urban, or other social groupings. Unless global declarations are clearly operationalized and efforts are made to strengthen a continuum between global and national goals and school and classroom practices, utter dependence on statistical data on gender, location, and other indicators of equity does not address ingrained challenges and opportunities for equitable quality education